Boundedness for some Schrödinger Type Operators on Weighted Morrey Spaces - Guixia Pan; Lin Tang (Journal of Function Spaces)
We establish the boundedness of some Schrödinger type operators on weighted Morrey spaces related to certain nonnegative potentials belonging to the reverse Hölder class.